Cómo producir un programa de radio - Araya Rivera, Carlos (2012)
Modern radio production requires better procedures for program recording. This article presents some theoretical and practical elements that facilitate professional and systematic production of radio messages and programs, thus they can be transmitted in cultural and commercial stations, in the traditional way (by broadcasting) or by podcasting.